1995
DOI: 10.1093/rheumatology/34.5.461
|View full text |Cite
|
Sign up to set email alerts
|

ANINUCLEAR ANTIBODIES IN EARLY ONSET PAUCIARTICULAR JUVENILE CHRONIC ARTHRITIS (JCA) ARE ASSOCIATED WITH HLA-DQB1*0603: A POSSIBLE JCA-ASSOCIATED HUMAN LEUCOCYTE ANTIGEN HAPLOTIYPE

Abstract: A panel of 43 early onset pauciarticular (EOPA) juvenile chronic arthritis (JCA) patients have been typed for human leucocyte antigens (HLA) DRB1, DPB1, DQA1 alleles, and DQB1*0603 status using molecular-based methods. Increased frequencies of DRB1*08 [odds ratio (OR) 7.7, 95% confidence interval (CI) 2.6-22.3], DRB1*11 (OR 3.1, 95% CI 1.2-8.1), DRB1*1301 (OR 7.7, 95% CI 2.6-22.3), DPB1*0201 (OR 3.5, 95% CI 1.6-8.0), DQA1*0103 (OR 4.4, 95% CI 1.5-13.3), DQA1*0501 (OR 2.9, 95% CI 1.3-6.6), DQA1*0601 (OR 30, 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The relationship between some of these alleles and autoimmune diseases has been reported. For example, DQ7.6 (DQA1*0601:DQB1*0301) is associated with asthma in Chinese population (43) and pauciarticular juvenile chronic arthritis without anti-nuclear antibodies (44). The allele of DQA1*0401 has been found associated with primary chronic progressive multiple sclerosis among the Ashkenazi patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between some of these alleles and autoimmune diseases has been reported. For example, DQ7.6 (DQA1*0601:DQB1*0301) is associated with asthma in Chinese population (43) and pauciarticular juvenile chronic arthritis without anti-nuclear antibodies (44). The allele of DQA1*0401 has been found associated with primary chronic progressive multiple sclerosis among the Ashkenazi patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygosity, at least with DR or DQ, does not result in increased risk for EOPA JRA and may even be protective (33). It should be restated that linkage disequilibrium is not involved with the susceptibility alleles discussed in this section, with the possible exception of DRB1*1301 and DPB1*0201 haplotypes (35). Fine mapping of the MHC genes in JRA, as a way of establishing the critical loci, is now possible.…”
Section: Polymorphic Markers In Jramentioning
confidence: 90%
“…Although the immunogenetic basis of JIA-associated uveitis has not been extensively investigated, a small study found that HLA DRB1*1301 allele is associated with ANA positivity, classically considered as a biomarker regarding the development of uveitis. 29 Another study has also found strong evidence supporting the involvement of HLA DRB1*13 in JIA-associated uveitis. 15 Several non-HLA susceptibility loci have been reported in association with JIA.…”
Section: Discussionmentioning
confidence: 93%